EFFECT OF TILLAGE AND METHODS OF FERTILIZER APPLICATION ON YIELD AND ECONOMICS OF HORSEGRAM - S.D.RAUT (The Journal of Research ANGRAU, 2016)
An experiment was conducted at Agronomy Farm of Dr. B.S.K.K.V., Dapoli during rabi season 2012-2013 to study the effort of tillage and methods of fertilizer application on yield and economics of horsegram.The field experiment was laid out in a split plot design with three replications. The main plot treatments comprised four tillage conditions - Minimum tillage with drilling (S1), Conventional tillage with drilling (S2), Conventional tillage with dibbling (S3) and Zero tillage (dibbling) (S4) and sub plot treatments comprised four methods of fertilizer application absolute control (F1 ), 100% RDF (Soil application) (F2), 25% RDF (Foliar application) (F3) and 50% RDF (Foliar application) (F4). The results revealed that tillage treatments conventional tillage with dibbling and conventional tillage with drilling was found significantly superior to rest of the treatments but at par with each other and recorded higher grain and straw yield, total cost of cultivation, gross income, net returns and B:C ratio obtained from different treatments. Among the methods of fertilizer application viz., 100% RDF (Soil application) and 50% RDF (Foliar application) were found significantly superior over remaining treatments but statistically identical with each other in respect of seed yield, total cost of cultivation, gross income, net returns and B:C ratio. It can be concluded that horsegram crop should be grown in conventional tillage condition by dibbling method along with soil application of 100 per cent recommended dose of fertilizer at sowing time, to obtain higher grain and straw yield, net returns and B:C ratio.